2018
DOI: 10.1111/imm.12998
|View full text |Cite
|
Sign up to set email alerts
|

Deceleration of glycometabolism impedes IgG‐producing B‐cell‐mediated tumor elimination by targeting SATB1

Abstract: B lymphocytes, known as antibody producers, mediate tumor cell destruction in the manner of antibody-dependent cell-mediated cytotoxicity; however, their anti-tumor function seems to be weakened during tumorigenesis, while the underlying mechanisms remain unclear. In this study, we found that IgG mediated anti-tumor effects, but IgG-producing B cells decreased in various tumors. Considering the underlying mechanism, glycometabolism was noteworthy. We found that tumor-infiltrating B cells were glucose-starved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The KEGG pathway is a collection of manually drawn pathway maps representing current knowledge on the molecular interaction and reaction networks and interpreting the data in the context of biological processes, pathways and networks. Twelve pathways were significantly enriched ( Figure 4A), and among these pathways, five pathways including cell cycle, cellular senescence, p53 signaling pathway, steroid hormone biosynthesis and pentose and glucuronate interconversions are widely reported to be correlated with the development and progression of several types of cancers (Kastan and Bartek, 2004;Lange et al, 2007;Munoz-Fontela et al, 2016;Calcinotto et al, 2019;Liu et al, 2019). In total, 23 DEGs were enriched in the five pathways; we selected all 23 genes ( Figure 4B) and performed GO enrichment analysis.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…The KEGG pathway is a collection of manually drawn pathway maps representing current knowledge on the molecular interaction and reaction networks and interpreting the data in the context of biological processes, pathways and networks. Twelve pathways were significantly enriched ( Figure 4A), and among these pathways, five pathways including cell cycle, cellular senescence, p53 signaling pathway, steroid hormone biosynthesis and pentose and glucuronate interconversions are widely reported to be correlated with the development and progression of several types of cancers (Kastan and Bartek, 2004;Lange et al, 2007;Munoz-Fontela et al, 2016;Calcinotto et al, 2019;Liu et al, 2019). In total, 23 DEGs were enriched in the five pathways; we selected all 23 genes ( Figure 4B) and performed GO enrichment analysis.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…Contrary to observations in solid tumors, SATB1 appears to suppress the progression of leukemia and lymphoma. SATB1 deficiency causes severe immunodeficiency and multiple defects in T-lineage development [1823]. We previously reported that SATB1 expressions were decreased in T cell leukemia/lymphoma (T-ALL), Knockdown of SATB1 significantly enhanced invasiveness of Jurkat cell in vitro [24].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Deletion of gene in mice would suppress the production of T cells, which lead to developmental disorder of thymus cells. 20,21 Besides, SATB1 played an important role in gene organization and could interact with proteins to specifically modulate the expression of target genes, which can act as transcriptional activator or suppressor depending on its specific genomic binding sites. 22,23 Accumulated evidence showed that SATB1 is an oncogene in the progression of various tumors.…”
Section: Discussionmentioning
confidence: 99%